Museum Kodam VI Mulawarman sebagai Sumber Belajar IPS Siswa Kelas VI - Nurul Faizah Yusran; Najamuddin Najamuddin; Bahri Bahri; Rasyid Rasyid; Patahuddin Patahuddin (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2025)
The purpose of this study was to evaluate the potential of the VI Mulawarman Military Command Museum as a source of Social Sciences (IPS) learning for grade VI students at SDIT Al-Auliya 2 Balikpapan. This research method uses a qualitative descriptive approach which is used to analyze the feasibility, utilization, and impact of this museum-based learning. The results of the study indicate that the museum provides a direct learning experience through a collection of historical artifacts such as weapons, documents, and dioramas, which can improve students' understanding of the history of the Indonesian people's struggle in Kalimantan. The use of this museum is also relevant to the Merdeka Curriculum, which emphasizes experiential learning and the relevance of the material to real life. Supporting factors for success include a rich collection, support from competent guides, and free access. However, obstacles such as limited guides and inadequate facilities need to be addressed immediately. The conclusion of this study is that the integration of museums in IPS learning can enrich students' understanding, strengthen their sense of nationalism, and support the formation of students' character in accordance with national values. Keywords: History, Kodam VI Mulawarman, Museum, Nationalism.